(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article focuses on the debatable problem of morphological status of the indeclinable words with stative meaning in modern linguistics. Different conceptions of defining their morphological nature are analyzed. Terminology for classifying these words is found out.